Efektivitas Rasio Jumlah Pasangan Induk Ikan Hias Black Tetra (Gymnocorymbus ternetzi) Terhadap Hasil Pemijahan [The Effectiveness Of The Ratio Of The Number Of Pairs Of Parents Of Pair Of Parents Of Black Tetra (Gymnocorymbus ternetzi) Against The Result Of Spawning] - Prayogo Prayogo (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract The purpose of this research is to know the effectiveness of the ratio of the number of pairs of parents against the result of the spawning of Black Tetra fish (Gymnocorymbus ternezi) about the number of egg produced, the rate conception (fertilization rate), the rate of hatching (hatching rate) and the survival rate of the fish (survival rate). The results shows that the ratio of number of pairs of black tetra fish parent has no effect but the greater the increase ratio of number of pairs of male parent black tetra fish then the number of eggs produced decrease.